Feasibility studied on production brood stocking Acipenser baerii in environmental condition Iran - Yazdani Sadati, Mohammad Ali; Mohseni, M.; Pourali, H.R.; Shakourian, M.; Pour Asadi, M.; Yousefi Jourdehi, A.; Halajian, A.; Sayed Hassani, M.H.; Pourdehghani, M.; Bahmani, M.; Kazemi, R. (Iranian Fisheries Science Research Institute, 2014)
This sturdy was carried out in three phases including evaluation of growth factors, determination of sexual hormone levels, caviar obtaining and reproducing of Siberian sturgeon (Acipenser baerii) brood stocks with the aims of brood stocks school production during 4 years. A total of 100 fingerlings with mean weight 1 kg were selected and reached to 2.5, 4 and 5.3 during 3 years, respectively. Steroid hormone levels such as testosterone (T), 11keto - testosterone (11- KT), estradiol (E2 ) and 17α-hydroxyprogestrone (17α-OHP) were measured for sexual development studying in males and females at different seasons during 3 years. Results showed that the most levels of 11- KT, E2 and T were observed at stage IV, III in summer and stage IV of sexual maturation, respectively, that was increased with sex development both in males and females. T levels showed significant difference between males and females (P< 0.05). At the third year of rearing, 31% of females were matured and 10 fish that their GV was between 6 to 9 were selected and injected with LHRH hormone. More than 90% of breeders had possitive response to hormone injection and 19500 larvae were produced from each fish. Larvae converted into fingerlings during 45 – 60 days. 8500 – 10500 fingerlings were produced from each breeder. Also some fish used for caviar obtaining. Results showed that the amount of caviar obtained from each fish was from minimum 6.8 % to maximum 10.3 % of body weight in Acipenser baerii. Iranian Fisheries Science Research Institute Published